Education on the impact of dangerous chemicals in food on health at Galesong Community Health Center, Galesong District, Takalar Regency, South Sulawesi: Edukasi dampak bahan kimia berbahaya pada makanan terhadap kesehatan di Puskesmas Galesong, Kecamatan Galesong, Kabupaten Takalar, Sulawesi Selatan - Surgani, Mishbah Nurul Fajri Surgani; ., Rahmawati; Dwijayanti, Endah; ., Mustaina; Zoraida, Masli Nurcahya (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2025)
Food Additives (FA) are ingredients added to food to influence the nature and shape of the food. The FAs that are often used are formalin, borax, artificial sweeteners and artificial coloring. This outreach program aims to provide education to the community at the Galesong Health Center about the dangers of adding hazardous chemicals. The method used is in the form of outreach with a two-way interactive method between the extension worker and the participants. The target of this outreach activity is the surrounding community and health center officers. The results of the community service show that the enthusiasm of the extension participants is very high with the activeness of the participants in the question and answer session. The education provided will become public knowledge in choosing good, safe and halal additives.